2001
DOI: 10.7863/jum.2001.20.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of sonographically detected breast masses using frequency shift color Doppler imaging in combination with age and gray scale criteria.

Abstract: Frequency shift color Doppler imaging was assessed in conjunction with patient age and gray scale (GS) features for discriminating benign from malignant breast masses. Thirty-eight women with sonographically detected masses scheduled for biopsy were evaluated using a 6-to 13-MHz scan head, and the masses were delineated in ultrasonographic image volumes. Vascularity in and around each mass was quantified using speed-weighted pixel density (SWD). Gray scale features were ranked visually on a linear scale. Combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…The 3D US data were acquired with an experimental system that was previously developed and tested at our institution (16,17). The 3D system consisted of a commercially available Logiq 700 (GE Medical Systems, Milwaukee, Wis) US scanner with an M12 linear-array transducer, a mechanical transducer-guiding system, and a computer workstation.…”
Section: D Us Imagingmentioning
confidence: 99%
“…The 3D US data were acquired with an experimental system that was previously developed and tested at our institution (16,17). The 3D system consisted of a commercially available Logiq 700 (GE Medical Systems, Milwaukee, Wis) US scanner with an M12 linear-array transducer, a mechanical transducer-guiding system, and a computer workstation.…”
Section: D Us Imagingmentioning
confidence: 99%
“…For large, highly attenuating lesions, the lower-frequency, wide field of view GE M7, 3-7 MHz, slightly curved matrix array was used. Both whole-volume gray scale and color Doppler image sets were acquired using the methods described by Bhatti et al [30]. The same procedure was performed after four cycles of chemotherapy.…”
Section: Ultrasoundmentioning
confidence: 99%
“…The same procedure was performed after four cycles of chemotherapy. The radiologist (MAR) selected the mass in each image volume and the volume and vascularity of the masses were computed using the method described previously [30].…”
Section: Ultrasoundmentioning
confidence: 99%
“…41,42 Studies in the past have shown that the efficacy of U.S. for discriminating breast masses is improved by adding the information from color flow Doppler imaging to the B-mode grayscale information than just from B-mode imaging. 43,44 In this study, color flow Doppler scans were performed at each time point to not only quantify the blood flow in and around the lesion, 45 but also to validate IVBaR of the 3D grayscale information in these color flow image volumes by the resulting alignment of the Doppler-imaged blood vessels that were not used in the registration. Previous studies have used information from major blood vessels in Doppler U.S. for fusing with MRI or computed tomography Ķ‘CTĶ’ images.…”
Section: Introductionmentioning
confidence: 99%